(3bUjOI GdHQOIs - (3GdUfgGLj GdHhUjQj GdeUQj, CHh YHO Gddg, TQa GdOjf , eMeO Hf SYjO Hf MeGO Hf YHO Gddg, (B696 (3g`s
(3ChdgG (B:s
(3jHOC Chdg YfO bhdg(B: (3aeG dYjfjc Ef bdJ GcaaG geJG (B*** (3heG dbdHc Ef bdJ GSJab Hges
(3BNQgG (B:s
(3hGNJe HNjQ dcd GdeSdejf ZOG (B*** (3aj GdcJH hGdGfHjGA hGdbOS hGdMQes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 139s
(3eYLe GdeDdajf(B: 3 / 317s
(3cTa GdXfhf(B: 2 / 1331s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs